The effects of thumb sucking habit on the development of malocclusions in preschool age children in Hilla city - Saba M Al-kinane; Zainab A. Al-Dahan (College of Dentistry/ University of Baghdad, 2019)
Background: habit is any purposeless action repeated unconsciously. It is a sign of lack of harmony between the subject and the surrounding environment. Deleterious oral habits such as finger sucking could be one of the etiological factors for altered oro-facial growth development. This study conducted to explore the association between finger sucking habit and malocclusion in deciduous dentition. Materials and method: Totally 40 chronic thumb sucker and 40 controls matching in age and gender were enrolled in the study. A study conducted by verifying different occlusal trait through the intra-oral examination. Thumb sucking habit diagnosed using data gathered from parents. Results: The statistical analysis showed a highly significant difference (p>0.01) in the occurrence of anterior open bite, increased over jet between study and controls, in addition to that thumb sucking habit increased the likelihood of development of anterior open bite, increased overjet and posterior cross bite by 39 folds, 40 folds and 3 folds respectively. Conclusions: Thumb sucking habit found to be a risk factor for the development of anterior open bite and increased overjet.